The association of nutritional factors and skin autofluorescence in persons receiving hemodialysis - Viramontes Hörner, Daniela; Selby, Nicholas M.; Taal, Maarten W. (Elsevier, 2018)
Objective: Advanced glycation end-products (AGEs) are uremic toxins that result from hyperglycemia, oxidative stress and systemic inflammation. AGEs are also formed in food during cooking. On the other hand, malnutrition may contribute to AGE formation through its association with oxidative stress and inflammation. AGE accumulation can be measured by skin autofluorescence (SAF) and elevated SAF is independently associated with higher mortality on hemodialysis (HD). We aimed to investigate associations between SAF, dietary AGE intake and markers of malnutrition in persons receiving HD. Design and setting: single center cross-sectional study. Subjects: 120 participants on HD dialyzing at least three times per week for 3-4 hours. Main outcome measures: SAF was measured using an Autofluorescence Reader. Dietary AGE, energy, protein and fat intake, handgrip strength (HGS), anthropometric measurements and biochemistry were also assessed. Subjective Global Assessment was performed to evaluate nutritional status. Results: SAF was higher in malnourished participants and correlated negatively with serum albumin and cholesterol, HGS and energy, protein and fat intake and positively with C reactive protein and chronological age; SAF did not correlate with dietary AGE intake. Multivariable linear regression analysis showed that diabetes, smoking, serum albumin, HGS, protein intake and dialysis vintage were independent predictors of increased SAF. Conclusions: Markers of malnutrition were more important determinants of increased SAF than high dietary AGE intake in this HD population. Nutritional interventions aiming to reduce SAF by correcting malnutrition should therefore be investigated. The observed association between higher SAF and malnutrition may in part explain the previously reported association between higher SAF and mortality on HD.